2022
DOI: 10.1002/rth2.12692
|View full text |Cite
|
Sign up to set email alerts
|

Platelet reactivity and platelet count in women with iron deficiency treated with intravenous iron

Abstract: Background Iron deficiency anemia (IDA) and heavy menstrual bleeding are prevalent, interrelated issues impacting over 300 million premenopausal women worldwide. IDA is generally associated with increased platelet counts; however, the effects of IDA and its correction on platelet function in premenopausal women remain unknown. Objectives We sought to determine how IDA and intravenous iron affect platelet count and platelet function in premenopausal women. Methods Hematologic indices were assessed in a multicen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…Iron has been rarely associated with the function of mature platelets, and there is a striking scarcity of literature on any relationships between iron and blood platelet reactivity [60][61][62]. However, on the other hand, iron is known to play an important role in megakaryocyte differentiation in the bone marrow [60].…”
Section: Discussionmentioning
confidence: 99%
“…Iron has been rarely associated with the function of mature platelets, and there is a striking scarcity of literature on any relationships between iron and blood platelet reactivity [60][61][62]. However, on the other hand, iron is known to play an important role in megakaryocyte differentiation in the bone marrow [60].…”
Section: Discussionmentioning
confidence: 99%
“…18 A study in premenopausal women showed the opposite effect, with lower platelet reactivity and adhesion under flow while iron deficient compared with the iron replete state. 19 Iron deficiency causes defects in the red cell membrane and decreased red cell deformability, which leads to abberant shear stress and vascular damage, which could also be an important contributor to thrombosis risk. 20 Patients in our study also had hypoalbuminemia at presentation, which could be due to protein loss in the gastrointestinal tract because of subclinical enterocolitis associated with cow's milk.…”
Section: Discussionmentioning
confidence: 99%
“…18 A study in premenopausal women showed the opposite effect, with lower platelet reactivity and adhesion under flow while iron deficient compared with the iron replete state. 19 Iron deficiency causes defects in the red cell membrane and decreased red cell deformability, which leads to abberant shear stress and vascular damage, which could also be an important contributor to thrombosis risk. 20…”
Section: Discussionmentioning
confidence: 99%
“…Preliminary findings demonstrated (1) intravenous iron repletion decreases platelet count in iron deficiency, (2) iron repletion significantly increases platelet integrin activation and alpha-granule secretion in response to adenosine di-phosphate (ADP) and collagen-related peptide and (3) platelet adhesion to type-1 collagen is enhanced after IVIT. 22 This suggests that iron is vital for optimal platelet function and haemostasis. We seek to understand that the alterations IVIT has on similar platelet profiles in injured patients, which has not previously been studied.…”
Section: Introductionmentioning
confidence: 99%
“…Recent work by our multidisciplinary team has identified several clinically relevant physiologic changes of platelets in iron-deficient premenopausal women which are reversed with IVIT. Preliminary findings demonstrated (1) intravenous iron repletion decreases platelet count in iron deficiency, (2) iron repletion significantly increases platelet integrin activation and alpha-granule secretion in response to adenosine di-phosphate (ADP) and collagen-related peptide and (3) platelet adhesion to type-1 collagen is enhanced after IVIT 22. This suggests that iron is vital for optimal platelet function and haemostasis.…”
Section: Introductionmentioning
confidence: 99%